Cross-Cultural Understanding Of Bipa International Students At Andalas University - Mayori, Syndi Putri; Tiawati, Refa Lina; Rahmat, Wahyudi (Journal of Humanity Studies, 2023)
This research is motivated by understanding the language and culture of other people in a society is very important, especially for international students who do not understand other languages and cultures that they encounter in other countries, for example how to act and behave. The position of international students is that they are individuals who enter and meet a new culture and situation. International students entering a new environment is not an easy thing, of course they need adjustments to face language and cultural differences. During this adjustment, international students usually experience culture shock or culture shock. Culture shock is a normal phenomenon for international students due to differences in language, culture, social environment and daily habits. This type of research is qualitative with descriptive methods. The respondent data in this research consisted of 3 BIPA international students. Data collection using observation, interview and documentation techniques. Data analysis uses the Miles and Huberman analysis model. Based on data analysis and discussion, the results obtained: Forms of cross-cultural understanding of BIPA international students at Andalas University 1) Patterns of perception in the results of interviews with BIPA international students, namely (a) recognizing Indonesian, (b) recognizing Indonesian culture, and (c) interpreting information about Indonesian language and culture 2) Conceptualization in the results of BIPA international student interviews, namely (a) interpreting differences in Indonesian language and culture, and (b) resolving an Indonesian language and culture problem 3) Communication in the results of BIPA international student interviews, namely (a) being able to speak Indonesian, and (b) can interact, international students interact well using two languages, namely Indonesian and English.